Hormone Levels and Ultrasound Evaluation of Caiman latirostris (Crocodylia, Alligatoridae) Ovulation - Portelinha, Thiago C.G; Jahn Graciela A; Hapon M. BelÃ©n; Verdade Luciano M; PiÃ±a Carlos I (South american journal of herpetology, 2015)
Although there is much information available about reproduction in Caiman latirostris, knowledge related to steroid hormone levels and follicle development for wild adult females is still lacking. In this study we monitored and assessed the development of follicles and eggs and correlated these results with plasma steroid hormone levels in 32 adult females captured in Santa Fe, Argentina. Fieldwork was carried out over two reproductive seasons (OctoberâJanuary) between 2010 and 2012. Using an ultrasound device to take images of the reproductive structures of adult females, we observed individuals with vitellogenic follicles (n = 5), eggs (n = 4), atretic follicles (n = 11), and inactive reproductive structures (n = 12). We found no reproductive females smaller than 65 cm snout-vent length. High levels of estradiol were found during the ovulation period (November) only in reproductive females. Reproductive females showed no differences in progesterone levels during the study period (NovemberâJanuary) compared to non-reproductive females; however, reproductive females showed higher progesterone levels during nesting (December). We found no differences in progesterone levels between reproductive females and females with atretic follicles at the end of the nesting period (January). Ultrasound imaging was found to be an efficient technique to study reproductive structures at the beginning of reproductive cycle of the broad-snouted caiman. Isolated analyses of hormonal levels are not sufficient to determine the reproductive condition of C. latirostris females.